CHANGE OF ORAL LIQUID PROPERTIES UNDER TREATMENTS DEVELOPED INFLAMMATION OF PERIODONTAL TISSUES IN PATIENTS CONSTRUCTIONS WITH FIXED DENTURE IN MOUTH CAVITY DYNAMICS - O. Petrushanko; S. Hermanchuk (Ukrainian Medical Stomatological Academy, 2015)
Abstract. In the article the author presents change of oral fluid properties under the influence of treatments developed inflammation of periodontal tissue in patients with fixed constructions of dentures in the mouth dynamics. Significant role in the development of inflammation in periodontal tissues was shown by data our studies. Oral liquid integrate external and internal factors of the pathogenesis of chronic catarrhal gingivitis. Thus, an important factor that determines the resistance to the destruction of the gums, is the composition and properties of saliva. The stability of its physical properties, in particular such as viscosity, is a prerequisite for the proper functioning of organs and tissues of the mouth. Increased oral fluid viscosity in patients with inflammation and gum recession that emerged against the background of orthopedic treatment defects dentition non-removable prosthesis designs can significantly impair its protective and cleansing function, which can lead in turn to the creation of abnormal situations in the mouth and increased risk of inflammation in periodontal tissues. At the same time, we can assume that exchange application offered treatments that include the use of hygienic elixir "Lisomucoid" mucosal gel "Flavogel" and iodine-containing drug "Ioddicerin" in the form of oral rinses and applications, stimulating the functional activity of salivary glands, which greatly improves the cleansing and protective functions of oral fluid and provides a balance of physiological processes in periodontal tissues. The research was tested in a clinical setting preventive measures, part of which is the use of personal hygiene and the use of mouthwash with anti-inflammatory action "Lisomucoid" mucosal gel "Flavogel" and iodine "Ioddicerin". Changes of mouth liquid properties treat the inflammation of periodontal tissue in patients with fixed constructions of dentures in the mouth found that oral fluid viscosity slightly, but increased in patients of all three age groups. However, most digital value of this indicator is a set in patients with non-removable dentures for 2 or 3 supporting the teeth, and the smallest in patients with single metal-ceramic crowns. In addition, an oral fluid viscosity change during treatment also depends on the age of patients. At the same time, the exchange of application offers treatments that include the use of hygienic elixir "Lisomucoid" mucosal gel "Flavogel" and iodine "Ioddicerin" in the form of oral rinses and applications, stimulate the functional activity of salivary glands and reduce the figure viscosity of 1.3 - 1.5 times, depend on the method of treatment, which greatly improves the cleansing and protective functions of oral fluid and provides a balance of physiological processes in periodontal tissues. Thus, drugs alone or in simultaneous combination simultaneously provide high clinical efficacy of the treatment of inflammation and gingival recession in patients with fixed constructions of dentures in the mouth.